2021
DOI: 10.1177/1363460720986927
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous data: Seeing social surveys through the sexuality prism

Abstract: Social surveys both reflect and shape beliefs about sexuality. Social norms construct the “authorized vocabulary” of surveys and the resulting data influence the research questions that can be answered and the policies likely to be inspired by study findings. Scholars have called for balancing attention to pleasure vs. danger and normative vs. non-normative practices in studies of sexuality as well as for collection of data on sexual desires, behaviors, and identities. We combine these calls into what we term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…These issues are by no means limited to SOGI data specifically or SGM health inequities: expanded investment in data-centered approaches within biomedicine touches on far-reaching social problems, including housing and food insecurity, education, employment, and race and ethnicity ( Table 1 ; Institute of Medicine, 2014 ; Cantor and Thorpe, 2018 ; NASDOH 2019 ; Douglas et al, 2015 ; Wasserman et al, 2019 ). In presenting a comparative case study of data-driven care, we unveil the deeply entrenched nature of biomedical stratification that continues to elude patient-level measurement and data standardization, joining other critical data scholars to call for deeper engagement with the social context of inequality ( Benjamin, 2019 ; Noble, 2018 ; Thompson, 2020 ; Westbrook, Budnick, and Saperstein 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues are by no means limited to SOGI data specifically or SGM health inequities: expanded investment in data-centered approaches within biomedicine touches on far-reaching social problems, including housing and food insecurity, education, employment, and race and ethnicity ( Table 1 ; Institute of Medicine, 2014 ; Cantor and Thorpe, 2018 ; NASDOH 2019 ; Douglas et al, 2015 ; Wasserman et al, 2019 ). In presenting a comparative case study of data-driven care, we unveil the deeply entrenched nature of biomedical stratification that continues to elude patient-level measurement and data standardization, joining other critical data scholars to call for deeper engagement with the social context of inequality ( Benjamin, 2019 ; Noble, 2018 ; Thompson, 2020 ; Westbrook, Budnick, and Saperstein 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While both scholars and measurement working groups note the multiple dimensions of gender and sexuality, including identity, attraction, behavior, and embodiment ( SMART 2009 ; FIWG 2016 ), the reporting mandate prioritizes population-identifying items given program focus on disparity monitoring. We note that the limited focus on patient identity as a means of assessing social difference fails to capture the full prism of gender and sexuality, including as these domains relate to the dynamics of stratification and associated inequity ( Westbrook, Budnick, and Saperstein 2021 ; Cruz, 2017 ; Paine, 2018 ).…”
Section: Tablementioning
confidence: 96%
“…Bisexuals were not grouped with lesbians and gay people because some research suggests that these groups differ in their support of liberal politics (Jones, 2021 ; Strolovitch et al, 2017 ; Swank, 2018b ) This measure places everyone into a single sexual identity and traces current sexual identities. The measure does not reveal if people based their sexual classifications on actions, desires, or any other criteria (Westbrook et al, 2022 ), but Egan ( 2008 ), Swank ( 2018b ) and Schnabel ( 2018 ) have shown that sexual identities are better predictors of political actions than other measures of sexual orientations.…”
Section: Methodsmentioning
confidence: 99%
“…Data came from the Time Series Study of the 2016 ANES (American National Election Survey). ANES is one of the few national random samples that addresses sexual identities and it is often considered one the most accurate sources of information on politics and sexual minorities (Schnabel, 2018 ; Westbrook et al, 2022 ). As a multisplit research design, ANES modified its survey items and data gathering modes throughout the 2016 elections.…”
Section: Methodsmentioning
confidence: 99%
“…Although many one-time, cross-sectional, victimization studies have begun to embrace SGM inclusivity (see DeKeseredy et al, 2021; Edwards et al, 2015; Langenderfer-Magruder et al, 2016; Martin et al, 2011; Porter & Williams, 2011; Ray et al, 2021; Walters et al, 2013), it is yet to be examined if larger data efforts, including multiyear national-level data collection, are following suit and measuring these concepts. A few studies (Aspinall, 2009; Westbrook et al, 2021; Westbrook & Saperstein, 2015) have examined major surveys to determine how gender, sex assigned at birth (hereafter referred to as “sex”), and sexuality have been conceptualized and measured over time. Although none of these studies focused on victimization, they serve as a guiding framework for how major surveys are measuring these vital concepts.…”
Section: Introductionmentioning
confidence: 99%